An analytical study of the common and unique characteristics of local studies centers in Central Luzon and CALABARZON regions - Perez, Martin Julius V.; Buenrostro, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
This study aimed to provide an overview and, at the same time, define and describe the common and unique characteristics, practices and status of local studies centers in Central Luzon Region (Region 3), and CALABARZON Region (Region 4a) of the Philippines. This study is intended to be a source of ideas and guidelines for the establishment of local studies centers in the future. It is in this light that this study focused on the mandates, structural characteristics, linkages, programs/services, programs/services beneficiaries, and management group's perceived extent of utilization of the five local studies centers in the two regions: Batangas Heritage Center (BHC), Cavite Studies Center (CSC), Center for Bulacan Studies (CBS) (Bahay-saliksikan ng Bulacan), Center for Central Luzon Studies (CCLS) and the Juan D. Nepomuceno Center for Kapampangan Studies (CKS).
This study conducted interviews with the management groups, did ocular visits and observation on the local studies centers, as well as document examination. The local studies centers were also analyzed based on the ideal functions, aims and objectives of local studies centers, as provided by Martin et al. (2002) and Foronda (1991).
The findings of the study identified the common and unique characteristics of the local studies centers. The common characteristics of the local studies centers include: a) having mandates for research coming from the university or college that houses them. b) having budget which usually comes from the university or college that houses them, c) having many linkages with different institutions, organizations, university, etc., particularly with the NCCA, and being member of KABANSA, d) having their own programs/services, which usually include having library materials/collection, conducting researches, conducting seminars and conferences, and having publications, e) having actual beneficiaries that are mostly students. f) having budget problems, and g) having research as the common purpose of the utilization of the local studies centers. The unique characteristics of each local studies centers include the following: For CBS: a) its vision, mission and objective statements are written in Filipino, b) its official name has an equivalent one in Filipino, c) its primary budget comes from its provincial government, d) it has only one permanent staff (the director), e) it is situated under the external affairs office of its university, and f) it houses the Filipiniana, Rizaliana and Bulcaniana collections of its university. For CCLS: a) its mandate does not show its geographical limitation in terms of local studies and comes from the need for a unit in its university to take charge of the museum, b) it has linkages in the field of social sciences, specifically political science, and c) it's programs/services' theme is poverty reduction. For CKS: a) its geographical scope includes the whole Kapampangan region, b) its mandates include preservation and promotion of its native language, c) it is directly under the office of the president and has a separate building of its own in the university which also has an established a library, archives, museum and theater. d) it has a travelling exhibit and releases Kapampangan song/music albums, and e)its budget is not a big problem. For BHC: a) it is under its university's Learning Resource Center, b) its director is called "head" instead of "director", c)it has linkages with institutions in the field of philosophy, and d) its programs/services include conducting heritage tours and conducting activities that concern its university's history, core values and identity. For CSC: a) its programs/services include providing consultancy and assistance in establishing local studies centers, and giving tribute to its local historians, and b) its main target beneficiaries are those people in the grassroots level.
Recommendations for this study include : a) providing and maintaining support from the mother institution, national and local government, and community, 6) addition of well-trained and properly-equipped personnel, e) marketing and promotion of the local studies centers, d) establishment of local studies centers in the country, e) standardization of the local studies centers, and f) continuous research on the local studies centers in the country.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Center for Bulacan Studies (Bahay-saliksikan ng Bulacan).; Center Central Luzon Studies; Juan D. Nepomuceno Center for Kapampangan Studies; Batangas Heritage Center; Cavite Studies Center; Local history